Korelasi Paritas dengan Kejadian Kanker Serviks di Yayasan Kanker Indonesia – Surabaya - Dessy Hidayati Fajrin (Akademi Kebidanan Aifa Husada Madura, 2020)
ABSTRACT Dangerous parity has more than two children or close birth distance, because it can cause changes in abnormal cells in the cervikx. Women who often have an increased risk of cervical cancer are higher (Priyanto, 2011). The purpose of this study was to determine the relationship of parity with the incidence of cervical cancer at the Indonesian Cancer Foundation. Corelational Analytic research design with a population of 35 people with a sample of 30 people using non-random sampling type Purpositive Sampling technique. Statistical test between variables using Spearman Rank with data scale and significance level α = 0.05 if the statistical result show ρ <0.05 then H0 is rejected, meaning there is a significant relationship between variables. The result of this study indicated that most women suffering from cervical cancer are Multipara, which is as much as 70% and diagnosed with stage 2 as much as 46.7% at the Indonesian Cancer Foundation. The Spearman Rank statistical test result show a significance valve of significance ρ = 0.00 < α = 0.05 means that H0 is rejected, which means there is a relationship between parity and cervical cancer incidence at the Indonesian Cancer Foundation. Furthermore, based on the Spearman Rank correlation coefficient, the value ρcalculated = 0.675 > ρtable 0.364 show that thefe is a relationship between parity and cervical cancer incidence.